Repair of Tobacco Carcinogen-Induced DNA Adducts and Lung Cancer Risk: a Molecular Epidemiologic Study - Qingyi Wei; Lie Cheng; Amos, Christopher I.; Wang, Li-E.; Zhaozheng Guo; Hong, Waun K.; Spitz, Margaret R. (JNCI : Journal of the National Cancer Institute, 2000)
Background: Only a fraction of cigarette smokers develop lung cancer, suggesting that people differ in their susceptibility to this disease. We investigated whether differences in DNA repair capacity (DRC) for repairing tobacco carcinogen-induced DNA damage are associated with differential susceptibility to lung cancer. Methods: From August 1, 1995, through April 30, 1999, we conducted a hospital-based, case–control study of 316 newly diagnosed lung cancer patients and 316 cancer-free control subjects matched on age, sex, and smoking status. DRC was measured in cultured lymphocytes with the use of the host-cell reactivation assay with a reporter gene damaged by a known activated tobacco carcinogen, benzo[a]pyrene diol epoxide. Statistical tests were two-sided. Results: Overall, lower DRC was observed in case patients than in control subjects (P<.001) and was associated with a greater than twofold increased risk of lung cancer. Compared with the highest DRC quartile in the control subjects and after adjustment for age, sex, pack-years of smoking, family history of cancer, and other covariates, reduced DRC was associated with increased risk of lung cancer in a dose-dependent fashion (odds ratio [OR] = 1.8 with 95% confidence interval [CI] = 1.1–3.1, OR = 2.0 with 95% CI = 1.2–3.4, and OR = 4.3 with 95% CI = 2.6–7.2 for the second, third, and fourth quartiles, respectively; Ptrend<.001). Case patients who were younger at diagnosis (<60 years old), female, or lighter smokers or who reported a family history of cancer exhibited the lowest DRC and the highest lung cancer risk among their subgroups, suggesting that these subgroups may be especially susceptible to lung cancer. Conclusion: The results provide evidence that low DRC is associated with increased risk of lung cancer. The findings from this hospital-based, case–control study should be validated in prospective studies.